The Impact of Dynamic Presentation Format on Consumer Preferences for Hedonic Products and Services - Roggeveen, Anne L.; Grewal, Dhruv; Townsend, Claudia; Krishnan, R. (Journal of Marketing, 2015)
Manufacturers and online retailers are readily availing themselves of new technologies to present their merchandise using a variety of formats, including static (still image) and dynamic (video) portrayal. Building on vividness theory, the authors propose and demonstrate that presenting products and services using a dynamic visual format enhances consumer preference for hedonic options and willingness to pay for those options. The dynamic presentation format increases involvement with the product/service experience in a manner presumably similar to that of the actual product experience. The result is an increased preference for and valuation of hedonic options. This holds true for experiential and search products in single and joint evaluations and carries over to subsequent choices. Across all studies, the results demonstrate that a dynamic (relative to static) presentation format enhances choice of the hedonically superior (vs. utilitarian-superior) option by more than 79%.